United Kingdom : Financial Sector Assessment Program-Basel Core Principles for Effective Banking Supervision-Detailed Assessment Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper provides detailed assessment of observance on the Basel Core Principles for Effective Banking Supervision. The current assessment took place during a period of continuing development and transition. It is based on the assessors' understanding of the current state of the supervisory approach, but also incorporates, where relevant, the available information about changes expected in the near future. Stress testing has become a critical supervisory tool that encourages firms and supervisors to adopt a more forward-looking view on the strength of their balance sheets and resilience to shocks. The emphasis on stress testing has encouraged firms to strengthen their internal analytical and risk-management capabilities.